Comparison Between Nano- and Micro-Sized Copper Particles as Fillers in NAO Friction Materials - Sanjeev Sharma; Jayashree Bijwe; Mukesh Kumar (Nanomaterials and Nanotechnology)
In this study, the comparative role of nano‐ and micro‐sized Cu powder in exploring the influence on the tribo‐performance of friction materials in the form of brake‐pads is discussed. Two friction composites were developed by keeping allthe ingredients constant and varying the size of the selected filler (copper powder). The developed micro‐composite contained 10 % (wt) Cu (400 ‐ 600 μm) while in the nano‐composite only a part (2